Corpus cavernosum smooth muscle cell dysfunction and phenotype transformation are related to erectile dysfunction in prostatitis rats with chronic prostatitis/chronic pelvic pain syndrome - Guang-chun Wang; Tian-run Huang; Yang-yang Hu; Ke-yi Wang; Heng Shi; Lei Yin; Bo Peng (BMC, 2020)
Abstract Background The relationship between chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and erectile dysfunction (ED) has been shown in many studies. However, the specific mechanism remains unclear. This study was to investigate the corpus cavernosum smooth muscle cell function and phenotype transformation in Experimental autoimmune prostatitis (EAP) rats. Methods EAP was induced in rats by using prostate protein supplemented with immuneadjuvant extraction, and the max-ICP and MAP were measured. IHC and Masson staining were done to assess inflammatory infiltration and collagen deposition in the corpus cavernosum, respectively. Subsequently, normal rat and EAP rat CCSMCs were purified by tissue block implantation and differential adherence method. The oxidative stress, smooth muscle phenotype transformation, cell cycle and intracellular calcium ion transport were also evaluated. Results The ratio of max ICP/MAP in EAP rats significantly reduced, and the TNF-α content and collagen deposition in the corpus cavernosum markedly increased as compared to healthy rats. High-purity rat CCSMCs were obtained. Oxidative stress was evident and the cGMP content decreased in the EAP rat CCSMCs. The expression of Cav1.2, IP3R1 and RyR2 increased, but the SERCA2 expression decreased in EAP rat CCSMCs, which was accompanied by increased intracellular calcium. Increased expression of OPN, collagen and KCa3.1, decreased Calponin expression and increased proportion of cells in the S phase were also observed in the EAP rat CCSMCs. Conclusion CP causes oxidative stress and imbalance of intracellular calcium in CCSMCs and promotes CCSMCs transformation from contractile to synthetic state, which may be involved in the pathogenesis of ED.